2020
DOI: 10.1073/pnas.2020204117
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring the specificity of extracytoplasmic function sigma factors

Abstract: Bacterial genomes are being sequenced at an exponentially increasing rate, but our inability to decipher their transcriptional wiring limits our ability to derive new biology from these sequences. De novo determination of regulatory interactions requires accurate prediction of regulators’ DNA binding and precise determination of biologically significant binding sites. Here we address these challenges by solving the DNA-specificity code of extracytoplasmic function sigma factors (ECF σs), a major family of bact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 53 publications
(88 reference statements)
2
21
0
Order By: Relevance
“…On the other hand, the region 2 sequence of HTZ78_05385 was close to an ECF sigma factor of another marine cyanobacteria, Nodularia spumigena , inferring the function of HTZ78_05385 is related to the adaptation to marine environment. Considering the promoter motifs predicted for clusters of ECF sigma factors, which had been clustered by region 2 and region 4 sequences in the previous study, we found 5′-GTC of − 10 motif and 5′-GGAAC of − 35 motif for SigG, and the extended − 10 and − 35 motifs for SigH; SigI and HTZ78_05385 were predicted to have 5′-CGTA of − 10 motif and 5′-CATCC of − 35 motif, which are distinctive from those of SigG and SigH ( Supplementary Figure 2C ) ( Todor et al, 2020 ).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…On the other hand, the region 2 sequence of HTZ78_05385 was close to an ECF sigma factor of another marine cyanobacteria, Nodularia spumigena , inferring the function of HTZ78_05385 is related to the adaptation to marine environment. Considering the promoter motifs predicted for clusters of ECF sigma factors, which had been clustered by region 2 and region 4 sequences in the previous study, we found 5′-GTC of − 10 motif and 5′-GGAAC of − 35 motif for SigG, and the extended − 10 and − 35 motifs for SigH; SigI and HTZ78_05385 were predicted to have 5′-CGTA of − 10 motif and 5′-CATCC of − 35 motif, which are distinctive from those of SigG and SigH ( Supplementary Figure 2C ) ( Todor et al, 2020 ).…”
Section: Resultssupporting
confidence: 52%
“…The SigG and other ECF sigma factors (SigH, SigI, and HTZ78_05385) were further analyzed to investigate their functions in stress responses. The amino acid sequences of region 2 and region 4, which are the conserved domains of ECF sigma factors, were aligned with previously known bacterial ECF sigma factors ( Todor et al, 2020 ). In results, it was revealed that both region 2 and region 4 sequences of SigG, SigH, and SigI of Synechocystis sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These specific ECF-promoter interactions at the -35 and -10 boxes have been recently explored to implement a tool for promoter prediction based on the amino acid composition of key DNA contact points within the σ 2 and σ 4 domains [50]. Its application has allowed the prediction of target regulons of nearly 70% of the known ECFs and established that around 55% of them are autoregulated.…”
Section: Transcription Initiation: σ 70 Factor Vs Ecfsmentioning
confidence: 99%
“…Altogether, this improvement in the classification will generally improve the ability of the scientific community to predict the function of newly annotated ECFs. Thus, it will help to: (i) define their target promoters based on over-represented motifs in those that are autoregulated, (ii) determine functionally important residues for this recognition and (iii) develop predictive tools to define target promoters, especially for those ECFs that are not autoregulated (a matter that has already started to be addressed [50]). Furthermore, a continuous update is guaranteed with the constantly increasing number of bacterial genome sequences.…”
Section: Ecf Classificationmentioning
confidence: 99%